Northern landscapes in transition: Evidence, approach and ways forward using the Krycklan Catchment Study - Laudon, Hjalmar; Hasselquist, Eliza Maher; Peichl, Matthias; Lindgren, Kim; Sponseller, Ryan; Lidman, Fredrik; Kuglerová, Lenka; Hasselquist, Niles J.; Bishop, Kevin; Nilsson, Mats B.; Ågren, Anneli M. (Hydrological processes, 2021)
Improving our ability to detect changes in terrestrial and aquatic systems is a grand challenge in the environmental sciences. In a world experiencing increasingly rapid rates of climate change and ecosystem transformation, our ability to understand and predict how, when, where, and why changes occur is essential for adapting and mitigating human behaviours. In this context, long‐term field research infrastructures have a fundamentally important role to play. For northern boreal landscapes, the Krycklan Catchment Study (KCS) has supported monitoring and research aimed at revealing these changes since it was initiated in 1980. Early studies focused on forest regeneration and microclimatic conditions, nutrient balances and forest hydrology, which included monitoring climate variables, water balance components, and stream water chemistry. The research infrastructure has expanded over the years to encompass a 6790 ha catchment, which currently includes 11 gauged streams, ca. 1000 soil lysimeters, 150 groundwater wells, >500 permanent forest inventory plots, and a 150 m tall tower (a combined ecosystem‐atmosphere station of the ICOS, Integrated Carbon Observation System) for measurements of atmospheric gas concentrations and biosphere‐atmosphere exchanges of carbon, water, and energy. In addition, the KCS has also been the focus of numerous high resolution multi‐spectral LiDAR measurements and large scale experiments. This large collection of equipment and data generation supports a range of disciplinary studies, but more importantly fosters multi‐, trans‐, and interdisciplinary research opportunities. The KCS attracts a broad collection of scientists, including biogeochemists, ecologists, foresters, geologists, hydrologists, limnologists, soil scientists, and social scientists, all of whom bring their knowledge and experience to the site. The combination of long‐term monitoring, shorter‐term research projects, and large‐scale experiments, including manipulations of climate and various forest management practices, has contributed much to our understanding of boreal landscape functioning, while also supporting the development of models and guidelines for research, policy, and management. The Krycklan Catchment Study (KCS, www.slu.se/Krycklan) is located in the heart of the Boreal region in northern Sweden. The field research infrastructure that started in 1980 consists of a 6790 ha catchment, and currently includes 10 long‐term monitored streams, ca. 1000 soil lysimeters, 150 groundwater wells, >500 permanent forest inventory plots, and a 150 m research tower for carbon, water and, energy flux measurements across different spatial scales. The purpose of KCS is to take a holistic approach to understand how changes in climate, land‐use, and air pollutants affect water quality, soil conditions, forest growth and biosphere‐atmosphere processes in the boreal landscape.